2002
DOI: 10.1093/cercor/12.10.1048
|View full text |Cite
|
Sign up to set email alerts
|

Brain Activity Underlying Encoding and Retrieval of Source Memory

Abstract: Neural activity elicited during the encoding and retrieval of source information was investigated with event-related functional magnetic resonance imaging (efMRI). During encoding, 17 subjects performed a natural/artificial judgement on pictures of common objects which were presented randomly in one of the four quadrants of the display. At retrieval, old pictures were mixed with new ones and subjects judged whether each picture was new or old and, if old, indicated in which quadrant it was presented at encodin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

58
233
3
7

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(301 citation statements)
references
References 49 publications
58
233
3
7
Order By: Relevance
“…Concerning hemisphere differences, the right hippocampus seems to be more clearly involved in the encoding and retrieval of objects in a spatio-temporal context as shown, for example, by Smith & Milner (1981) with respect to patients with right hippocampal lesions and by Cansino et al (2002) by means of fMRI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning hemisphere differences, the right hippocampus seems to be more clearly involved in the encoding and retrieval of objects in a spatio-temporal context as shown, for example, by Smith & Milner (1981) with respect to patients with right hippocampal lesions and by Cansino et al (2002) by means of fMRI.…”
Section: Discussionmentioning
confidence: 99%
“…However, other structures involved in the encoding/retrieval aspects of Episodic Memory (EM) also show such biases. For example, Burgess (2002), Brewer et al (1998), andCansino et al (2002), have argued that the hippocampus might be a physiological structure mediating episodic memory (EM). In line with this assumption O'Reilly, Braver and Cohen (1998) included a sub-network in their connectionist model that parallels the hippocampal structure and, most important, this sub-network learns new patterns, by "taking snapshots" of the entire activation pattern in the rest of the network and by storing them as episodes.…”
Section: Discussionmentioning
confidence: 99%
“…Several prior neuroimaging studies have revealed increased hippocampal activation during associative encoding (45,46,56). However, few studies have examined the specific contributions of MTL encoding mechanisms to recognition (57)(58)(59)(60), and none have observed hippocampal correlates specific to later recollection. In the present study, hippocampal encoding responses predicted whether subjects would be able to subsequently recollect the source associated with an item's prior encounter, consistent with the putative role of hippocampus in conjunctive learning that supports later pattern completion.…”
Section: Discussionmentioning
confidence: 99%
“…Wagner et al (2005), following Rugg and colleagues' lead (e.g., Rugg & Wilding, 1996) pointed out that in at least some lateral parietal areas, activation tends to be greater when participants are required to retrieve information about the specific contextual details associated with an event, such as remembering which of two actions one performed in relation to a stimulus at encoding (Dobbins, 2003) or in which spatial location a stimulus was studied (Cansino et al, 2002; see also Hayes et al, 2004). This possibility also fits with classic interpretations of the heteromodal role of parietal cortex, in which it posited to act as a crossroads, integrating information from multiple sensory domains (Critchley, 1953).…”
Section: Current Theories Of the Lateral Parietal Region's Role In Mementioning
confidence: 96%